Renovate or defeat: about creation of Russian Imperial bureaucracy and “domino principle” in Petrine reforms - D. Yu. Znamenskiy (Вестник университета)
The article considers the process of reforming the civil service in the context of the state transformations of Peter the Great. The author pays special attention to the periodization of reforms. Based on its analysis, the conclusion is drawn not only about the validity of the chronological division of Peter the Great’s state transformations into conditionally spontaneous and organized stages, but also about a kind of “domino principle”: the implementation of one reform necessitated the next. The author gives his own interpretation of the features of the formation of the imperial bureaucracy in Russia in the first quarter of the XVIII century. The relatively slow development of this process is noted, which can be explained by the inertia of the bureaucracy itself and, first of all, the podyachy corps.